Investigation of Color Fading and Fabric-Touch Test for Jeans through Ozonation. (4th May 2021) - Hu, Lizhu; Zhou, Xinyi; Chen, Juanfen; Zhang, Xiuling; Chen, Guoqiang; Chang, William; Ye, Alice; Yi, Hong; Yi, Changhai
ABSTRACT: Color fading through ozonation has been previously studied by our and other labs. Although great progress has been achieved in this field, studies for the optimization of the operating process of the ozone water washing process and fabric-touch tests are important for the practical application in industry. An industrial-scale G2 ozone washing machine was used for the color fading of the samples. Since the color fading process factors are interrelated to each other, a specific experimental approach, i.e., orthogonal method, was used in this work. Three process factors used in the industrial scale color fading process, i.e. (i) ozone feed rate; (ii) moisture content in the fabric; and (iii) treatment time, were studied in this paper. Additionally, the color fading and tactility of fabric through ozonation were analyzed Our results show that the three investigated factors have a significant impact on the fading effect, in which the treatment time is the most significant. When using the G2 device for denim washing, the desired color-fading effect could be quickly obtained by adjusting the treatment time at 6.67 g/min of ozone feed rate and 50% of moisture content in the fabric. Finally, the tactile analysis by fabric-touch tester shows that there is no significant change in the total touch feel between the treated samples and the untreated sample.